Anomalous reduction in the long-time flux creep relaxation in superconducting Ca10(Pt4As8)((Fe1−x Ptx )2As2)5 (x ≈ 0.05) single crystals - Haberkorn, N. (2018)
Fil: Haberkorn, N. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina